2020
DOI: 10.1139/facets-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

A molecular assessment of infectious agents carried by Atlantic salmon at sea and in three eastern Canadian rivers, including aquaculture escapees and North American and European origin wild stocks

Abstract: Infectious agents are key components of animal ecology and drivers of host population dynamics. Knowledge of their diversity and transmission in the wild is necessary for the management and conservation of host species like Atlantic salmon ( Salmo salar). Although pathogen exchange can occur throughout the salmon life cycle, evidence is lacking to support transmission during population mixing at sea or between farmed and wild salmon due to aquaculture exposure. We tested these hypotheses using a molecular appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 122 publications
(128 reference statements)
2
16
0
Order By: Relevance
“…2008 ), so it is not surprising that they are found extensively in all groups of vertebrates and cause a wide variety of diseases in mammals and birds ( Wolf et al. 2009 ; Tse et al. 2012 ; Scheuer et al.…”
Section: Discussionmentioning
confidence: 99%
“…2008 ), so it is not surprising that they are found extensively in all groups of vertebrates and cause a wide variety of diseases in mammals and birds ( Wolf et al. 2009 ; Tse et al. 2012 ; Scheuer et al.…”
Section: Discussionmentioning
confidence: 99%
“…PRV prevalence in wild Atlantic Salmon of Eastern North American is limited. In a recent study, PRV was not detected in 60 returning wild Atlantics salmon screened in New Brunswick, suggesting that prevalence would be 5% or less in that cohort (Teffer et al., 2020). In contrast, multiple molecular screening studies of wild‐caught Pacific salmon and trout from western North America involving almost 13,000 specimens have demonstrated that PRV‐1 detection can vary dramatically between species and stocks in this region.…”
Section: Prevalencementioning
confidence: 98%
“…Retrospective screening of eight Atlantic Salmon diagnosed with haemorrhagic kidney syndrome from two farmed populations in New Brunswick in 1996 was all shown to be positive for PRV nucleic acid and protein (Ferguson et al., 2020). More recently, PRV has been detected in escaped farmed Atlantic Salmon (Teffer et al., 2020) and in most other instances where net‐pen farmed Atlantic Salmon have been screened (N. Gagne, personal communication), suggesting that PRV‐1 is likely ubiquitous in farmed Atlantic Salmon in the region and has been so for at least the last few decades.…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations